Influence of stimulated plasticity training method on coordination indicators of high pedagogic educational estableshments’ girl students - A.N. Kolumbet (Physical Education of Students, 2015)
Purpose: study of stimulated plasticity training’s influence on coordination indicators of pedagogic HEEs’ girl students. Material: 264 girl students participated in the research. Experiment was being carried out during three years. Responding abilities, static and dynamic balance, orientation in space, promptness of operative thinking, volume of mechanical memorizing, distribution of attention, accuracy, quickness and of attention re-switching, accuracy of tasks’ fulfillment were assessed. Results: it was found that plasticity has different kinds and forms of manifestation. Creative motor tasks require different conditions for their realization. We determined rates of plasticity increment by its main kinds. Plasticity of body movements was achieved at high level of different muscular groups’ coordination, optimal rhythm, rational correlation of tension and relaxation. Conclusions: it was found that plasticity shall be trained in compliance with its kinds and manifestations. It requires appropriated approach to content of methodic of its perfection.